Teamwork and generic skills in engineering students - Graciano García, Samuel Josué (2022)
Society is constantly changing, in such a way that it requires competent professionals in the future, capable of working cooperatively, contributing with knowledge and innovations. The objective of this study was to determine the relationship between teamwork and generic skills in engineering students. The quantitative approach of correlational design was used, for which a census sample of 106 engineering students was used, to whom two Likert scale questionnaires were applied. The results obtained a Spearman correlation of .342. It was concluded that there is a low significant relationship between teamwork and generic skills in Engineering students.